Analysis of Crude Oil Prodction in Nigeria by Servicing Companies (Global Journal of Science Frontier Research, 2021)
The petroleum industry in Nigeria has brought unprecedented changes to the Nigerian economy, particularly in the past five decades when it replaced agriculture as the cornerstone of the Nigeria economy. The oil industry has risen to the commanding heights of the Nigerian economy, contributing the lion share to gross domestic product and accounting for the bulk of federal government revenue and foreign exchange earnings since early 1970. However, Nigeria's considerable endowment in fossil fuel has not translated into an enviable economic performance; rather, the nation's mono-cultural has assumed a precarious dimension in the past decades susceptible to the vagaries of the international oil markets. Empirical analysis was conducted by applying the Multiple Linear Regression of the Ordinary least square techniques, the joint distribution of independent variable contribute to the success of the total production prob(F. Statistic) = 0.00122 which is less than 0.05 thereby establishing the significance of the independent variable. Conclusively, the Servicing Company relationship is not the same, also from estimated regression line only x 2 (Joint Ventures AF/CARRY and x 5 (Sole Risk Independent Companies) has the highest coefficient which implies that they have greater contribution to the total production.
Keywords: crude oil; foreign exchange earnings; multiple linear regression; servicing; company; total production